Digital Medication Reminders to Improve Antiretroviral Therapy Adherence in Children Living with HIV: Literature Review - Rahmawani, Atika; Islamia, Ina; Ningsih, Risna (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2025)
Background: Antiretroviral treatment is the treatment for people infected with human immunodeficiency virus (HIV) using anti-HIV combinations that are used for life. The main factors determining the success of ARV treatment are sustained and optimal adherence to therapy. Adherence to ARV treatment can be challenging for children and especially adolescents with HIV because ARVs must be taken for life. There are several ways to improve adherence to ARV medication directly, namely through comprehensive educational pressure, other ways can be done by utilizing technology that uses medication reminder applications such as the use of smartphones, android-based application development, electronic monitoring, Short Message Service (SMS), social media-based support, and mass media campaigns. This paper reviews the scientific evidence on technology-based ARV treatment adherence. Methods: This article is based on scientific journal searches conducted through online databases, namely Scopus, Proquest, PubMed, and Scholar, published in 2019-2023. Results: showed that using technology as a reminder to take medication can improve adherence of children with HIV in taking ARV drugs. Conclusion: The use of technology can improve adherence in children with HIV, can also reduce viral load rates, and increase CD4 levels